2016
DOI: 10.1038/leu.2016.327
|View full text |Cite
|
Sign up to set email alerts
|

Complementary activities of DOT1L and Menin inhibitors in MLL-rearranged leukemia

Abstract: Chromosomal rearrangements of the mixed lineage leukemia (MLL/KMT2A) gene leading to oncogenic MLL-fusion proteins occur in ~10% of acute leukemias and are associated with poor clinical outcomes, emphasizing the need for new treatment modalities. Inhibition of the DOT1-like histone H3K79 methyltransferase (DOT1L) is a specific therapeutic approach for such leukemias that is currently being tested in clinical trials. However, in most MLL-rearranged leukemia models responses to DOT1L inhibitors are limited. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 52 publications
2
84
0
1
Order By: Relevance
“…80 Instead, a combinatorial approach of therapies targeted towards different pathways, and/or in addition to conventional cytotoxic chemotherapeutics is likely to prove an optimal approach. Inhibitors targeting HDAC, 102 BET, 103,104 and menin 81…”
Section: Dot1l Inhibitorsmentioning
confidence: 99%
“…80 Instead, a combinatorial approach of therapies targeted towards different pathways, and/or in addition to conventional cytotoxic chemotherapeutics is likely to prove an optimal approach. Inhibitors targeting HDAC, 102 BET, 103,104 and menin 81…”
Section: Dot1l Inhibitorsmentioning
confidence: 99%
“…In this report, we characterize the mechanism of action of MI-2, a drug previously identified in a small molecule screen, as having a therapeutic effect in preclinical DIPG and glioma models. Elegant studies have demonstrated MI-2 is a menin inhibitor (7,8), and in MLL-fusion leukemia cells, interruption of the menin-MLL interaction has a well-established mechanistic link to suppression of leukemia growth (7,8,12,13,29). In the context of glioma, however, although menin is expressed, our data show it is not a major target responsible for the antitumor effects observed after MI-2 treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Targeting more than one component of the KMT2A complex has great potential for targeted treatment. Although a DOT1L inhibitor by itself has not shown promising results in Phase I trials, Dafflon et al showed that the combination of a DOT1L inhibitor and a menin inhibitor demonstrated robust synergy in its anti-leukemic growth inhibition effect in a mouse model injected with KMT2A-AF9 leukemic cells, compared to either drug alone [44,52]. Further studies will be needed to investigate whether the combination of Pinometostat with another anti-leukemic agent can improve its efficacy.…”
Section: Targeting Kmt2a-fusionmentioning
confidence: 99%